2002
DOI: 10.1046/j.1365-2516.2002.00642.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of chronic disease on the family

Abstract: resUMen Se describen las alteraciones estructurales y emocionales de las familias con uno o más miembros enfermos de Huntington, en función de los diferentes síntomas, del afectado (descendientes, progenitores) y de las diferentes etapas. Consideramos que los servi-cios de ayuda a la familia deben estar compuestos por profesionales expertos en las necesidades específicas de esta enfermedad y que deben ayudar a planificar y diseñar las ayudas de manera individual, adecuada y flexible. Esta ayuda debe centrarse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 18 publications
4
34
0
Order By: Relevance
“…The fact that haemophilia has an impact on PWHs and those around them, both in their functioning and daily activities, is widely acknowledged . People who grow up with haemophilia, sometimes accompanied by an infectious disease, often experience social stigma and fear of rejection .In some societies, the man is traditionally expected to financially support his family, and the disease might make it difficult for him to fulfil this role.…”
Section: Issues and Counselling Of The Adult With Haemophiliamentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that haemophilia has an impact on PWHs and those around them, both in their functioning and daily activities, is widely acknowledged . People who grow up with haemophilia, sometimes accompanied by an infectious disease, often experience social stigma and fear of rejection .In some societies, the man is traditionally expected to financially support his family, and the disease might make it difficult for him to fulfil this role.…”
Section: Issues and Counselling Of The Adult With Haemophiliamentioning
confidence: 99%
“…Haemophilia is a condition usually diagnosed during childhood, and psychosocial aspects of the early years have attracted much attention in the literature. Many authors , including our group , have addressed the psychological impact of the disease, and the necessary support for the family and young patient as he experiences growing up with haemophilia from infancy, through childhood and adolescence . However, the issues of adults or ageing persons with haemophilia (PWHs) have been less frequently discussed.…”
Section: Introductionmentioning
confidence: 99%
“…According to Goldstein G et al have reported that recurrent joint bleeds, change of physical appearance are associated with isolation, depression, anger, and aggressiveness among children with hemophilia. 13 Mothers are reported to bare the maximum burnt due to nature of transmission, resulting in accusations of boys and the family members and associated guilt and isolation within the family. Canclini M et al have reported a lower self-esteem, which tends to increase with age in hemophilic children, as compared to healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…When a child is initially diagnosed, shock, denial, anger and depression are common emotional responses of the parents [79] that play a significant role in the care of a child with hemophilia and refers to experiencing a large responsibility for management of hemophilia at home [80]. Parents have to face not only feelings of anxiety, guilt and worry over their child’s condition, but also the impact of pain during infusion [81].…”
Section: Psychological Issuesmentioning
confidence: 99%